2005
DOI: 10.1002/sia.2026
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural analysis of a carbon fibre reinforced AZ91D magnesium alloy composite

Abstract: Interfacial regions in metal matrix composites are important in controlling the mechanical and thermal properties of these materials. An ultrahigh modulus fibre-reinforced magnesium alloy matrix composite has been studied, with particular attention paid to the interfacial and precipitate microstructures. Fibres were surface treated but uncoated prior to composite manufacture. Observations revealed that an interface consisting of polycrystalline magnesium oxide with occasional Mg 17 Al 12 (b) precipitate partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Thus, CNTs particles prevent the production of β phases, as evident from XRD results. Numerous investigators reported the formation of carbide, Al 4 C 3 [26] and Al 2 MgC 2 [27]. In order to confirm the carbide formation, transmission electron microscopy (TEM) was carried for Mg3Al-1Zn-1.0CNTs composite as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, CNTs particles prevent the production of β phases, as evident from XRD results. Numerous investigators reported the formation of carbide, Al 4 C 3 [26] and Al 2 MgC 2 [27]. In order to confirm the carbide formation, transmission electron microscopy (TEM) was carried for Mg3Al-1Zn-1.0CNTs composite as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The interfacial state between magnesium alloy and carbon nanotubes was also considered, because the formation of carbide (Al 2 MgC 2 ) was reported when the temperature was >773 K and the aluminum level in magnesium alloy compositions was >0.6 % and <19 % [25].…”
mentioning
confidence: 99%
“…According to the phase diagram of alloy AZ91D, the main constituents of the matrix alloy are the primary solid solution (a-Mg) and lamellar eutectic (constituted by a-Mg and b-Mg 17 Al 12 ). The interfacial region includes the precipitated phase (b-Mg 17 Al 12 ) and reactive phase (Al 4 C 3 ), which has been verified by SEM, EDS and TEM in literatures [27,28]. The endothermic peak at low temperature on the heat flow curve (in Fig.…”
Section: Remelting Behaviormentioning
confidence: 77%